Prevalence of COVID-19 vaccines side effects among health care workers in Kirkuk City, Iraq - Mohamdamen-Ameen, Omed Hamarasheed; Hasan, Nashwan Nadhim; Ismael, Zhyan Abdullah (Intelektual Pustaka Media Utama, 2024)
Frequent local and general side effects were revealed after vaccination with COVID-19 vaccine, which played a role in public confidence in and acceptance of the vaccine since the evidence source for the safety of the vaccines and their side effects were exclusively provided only from manufacturer-funded researches. This study aimed to assess the prevalence of COVID-19 vaccines side effects among health care workers in Kirkuk City, Iraq. This cross-sectional study was done in governmental hospitals in Kirkuk City/Iraq from May 7, 2022 to August 15, 2022 among 373 healthcare workers (only those who were vaccinated with the COVID-19 vaccine). The data were analyzed through the statistical package for social sciences (SPSS) program version 23.0. Total of 246 (66%) healthcare workers experienced at least one side effect following the COVID-19 vaccination. Reported side effects among females were higher (70.1%) than males (60.4%) and they were a little higher (67.2%) among participants with age ≤40 years. The most repeated side effects were general fatigue, injection site pain, and headache. In conclusion the majority of the reported side effects were mild to moderate in severity and not considered life-threatening. The rate of COVID-19 side effects was lower among the participants who received Sinopharm's COVID-19 vaccine in comparison to others vaccines.